ANALISIS PERANCANGAN TUNGKU PENGECORAN LOGAM (NON-FERO) SEBAGAI SARANA PEMBELAJARAN TEKNIK PENGECORAN - Ramang Magga (Program Studi Matematika, Universitas Tadulako, 2010)
Casting is a manufacture process that use liquid metal and mold to shape product as similar as its final geometric shape. That casting product is melted in a furnace before it is shaped. This research aims to analyze furnace design. Furthermore, external shape of the furnace is planned 50 cm x 50 cm and shape of the furnace inside is cylinder with diameter 20 cm. The furnace is expected as learning facility of welding for students